Analysis on the thrust bearing lubrication in pumped storage unit based on fluid-solid-thermal interactions. Issue 1 (January 2021) - Cao, J W; Zhai, L M; Guo, B; Lei, H M; Ahn, S H; Wang, Z W
Abstract: The bidirectional thrust bearings are used to balance the thrust load of the entire shaft system which play an important role in the pumped storage units. The lubrication is usually analyzed by simultaneously solving the Reynolds equation, energy equation, film thickness equation of the film and the heat conduction equation, elastic equilibrium equation of the pad. However, in this method the assumptions for the inlet temperature of the film and the wall heat coefficients on the pad greatly affect the numerical accuracy. This study used fluid-solid-thermal interaction method, built three dimensional (3D) FEM model for the pad and collar and the 3D CFD model for the oil film, and then analyzed the influence of the thrust loads and the Babbitt layer on the bearing performance. The results show that increasing the thrust load will rapidly decrease the minimum film thickness, increase the maximum pressure and maximum temperature on the pad. Increasing the thickness of the Babbitt layer on the pad sliding surface will increase the minimum thickness of the film, decrease the maximum temperature on the pad which improve the bearing lubrication.